The Enhancing Vocabulary Mastery Through Seamless Learning: A Digital Approach to English Language Instruction - al ausi, Muhammad berlin al ausi; Lailatul Maimunah; Muamar Chadafi (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study investigates the effectiveness of the seamless learning strategy in enhancing students’ vocabulary mastery within an English language learning context. Seamless learning, characterized by the integration of formal and informal learning through mobile technology and online collaboration, offers continuous access to learning resources and supports personalized learning pathways. Employing a pre-experimental design with a one-group pre-test and post-test model, this research involved 30 junior high school students. Quantitative data were collected using vocabulary tests administered before and after the implementation of the seamless learning intervention. The findings revealed a significant improvement in students' vocabulary performance, with mean scores increasing from 52.00 in the pre-test to 82.67 in the post-test. A paired sample t-test analysis confirmed the statistical significance of this gain (Sig. 2-tailed = 0.000, p < 0.05). These results suggest that seamless learning effectively fosters vocabulary acquisition by promoting learner autonomy, motivation, collaboration, and contextual engagement. The study also discusses pedagogical implications and highlights the need for future research with larger samples, extended implementation periods, and qualitative analyses. Overall, the findings support the adoption of seamless learning as an innovative and impactful strategy for improving vocabulary instruction and language proficiency in 21st-century educational settings.